Longitudinal effects of physical activity on self-efficacy and cognitive processing of active and sedentary elderly women - Rosanti, Sofia [UNESP]; Silva, Guilherme Elias da; Santos, Flávia Heloísa dos [UNESP] (FapUNIFESP (SciELO), 2014)
Previous studies support that regular physical activity in aging contributes as a protective factor against cognitive decline and improves mood states. However, there is a lack of longitudinal studies in this area. Objective: To observe possible changes in cognition related with physical activity. METHODS: This study reassessed, after one-year period, 31 elderly women divided into two groups, sedentary versus active, using behavioral scales and cognitive tests. RESULTS: The active group exhibited significantly enhanced performance in general cognitive function, particularly on tasks of episodic memory and praxis, and also on the mood states scale compared to the sedentary group. The active women also reported higher self-efficacy. CONCLUSION: Long-term physical activity promoted improvement on quality of life in the elderly women.

Estudos anteriores sustentam que a prática regular de exercícios físicos contribui como fator de proteção aos declínios cognitivos e melhoras no estado de humor no envelhecimento. Contudo, há uma carência de estudos longitudinais nesta área. Objetivo: Observar possíveis alterações na cognição em relação a atividade física. MÉTODOS: O PRESENTE ESTUDO REAVALIOU APÓS UM ANO 31 IDOSAS DIVIDIDAS EM DOIS GRUPOS, SEDENTÁRIAS VERSUS ATIVAS, POR MEIO DE ESCALAS COMPORTAMENTAIS E TESTES COGNITIVOS. RESULTADOS: HOUVE UM DESEMPENHO SIGNIFICATIVAMENTE MELHOR EM IDOSAS ATIVAS EM FUNÇÕES COGNITIVAS GERAIS, MAIS ESPECIFICAMENTE EM TAREFAS DA MEMÓRIA EPISÓDICA E PRAXIA, COMO TAMBÉM PARA A ESCALA DE ESTADO DE HUMOR, EM COMPARAÇÃO COM O GRUPO DE SEDENTÁRIAS. O GRUPO DE ATIVAS TAMBÉM APRESENTOU MAIOR AUTO EFICÁCIA. CONCLUSÃO: PRÁTICAS DE ATIVIDADES FÍSICAS A LONGO PRAZO PROMOVEU MELHORA NA QUALIDADE DE VIDA DE IDOSAS.
Estudo longitudinal sobre efeitos da autoeficácia e da prática de atividades físicas no processamento cognitivo de idosas ativas e sedentárias
Keywords: Aging; Physical activity; Self-efficacy; Episodic memory; Praxis; Envelhecimento; Atividades físicas; Auto eficácia; Memória episódica; Praxia